IL-6 Level and the Risk of Arthritis after COVID Infection (Journal of Pharmaceutical Negative Results, 2022)
We aimed to assess the prognosis on the onset of arthritis in the diabetic patient after severe SARS-CoV-2 infection.Methods: The medical data of 10 patients with type 2 diabetes melitus, obese or overweight, hospitalized, in the interval between 1st of February and 31st of July 2021 at ``Saint Spyridon`` County Hospital Iasi, Romania for SARS-Cov-2 infection with were analyzed.Results: Although all the patients received treatment with tocilizumab 8 mg/kg body during 30 days, the blood analysis showed very high level of interleukins 6, and the joint painful symptoms continued to be manifested. The interleukins 6 serum level is higher and persistent in diabetic patient with SARS-CoV-2 infection, against the background of pre-existing chronic inflammation induced by diabetes, obesity and the glycemic imbalance. This renders the cytokine release syndrome difficult to control in the diabetic patients with severe infections, which leads to a higher hazard of interleukin 6 transcription errors. SARS-CoV-2 diabetic patients run the risk of developing long-term arthritis due to the uncontrolled, permanent synthesis of this cytokine.Conclusion: The immunologic modifications associated with the severe coronavirus infection acting on the predisposing genetic background (HLA-DR4/DR1), might underlie the onset of the arthritis on the long-term due to the exaggerated activation of IL-6 and the chronicity of the inflammation it generates. Studies shall be required that monitor on the long-term the diabetic patients surviving a severe Sars-CoV-2 infection as to the occurrence of the arthritis.